Pengaruh Motivasi dan Minat Belajar terhadap Prestasi Belajar PKn Peserta Didik Sekolah Dasar - Tri Love Putrawan Gea; Cindi Sheren Solinia Halawa; Vica Tri Putri Zega; Desti Dahliana Telaumbanua; Yola Arisandy Gea; Desrakna Sari Laoli; Yernima Lombu; Risman Setiawan Zega; Edward Harefa (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
The point of this investigate is to clarify the impact of students' inspiration and intrigued in learning on scholarly accomplishment within the field of Civics. This sort of inquire about employments quantitative inquire about utilizing overview procedures. The different relationship measurable test was utilized to test information investigation. The information collection strategies utilized in this investigate were surveys and dispersing surveys. In other words, Ho is rejected and Ha is acknowledged, which suggests that intrigued and inspiration to memorize impact the Civics learning accomplishment of basic school understudies.